Bird exploitation in Viljandi (Estonia) from the Late Iron Age to the early modern period (c. 950–1700). (20th July 2022) - Ehrlich, Freydis; Rannamäe, Eve; Valk, Heiki
Abstract: This paper examines archaeological bird bones from Viljandi – one of the strongest centres in prehistoric and medieval Estonia – and covers material from the Late Iron Age to Early Modern Period, c. 950–1700. Over 5000 bird bones were analysed in this study. Our main aim was to explore the role of birds in people's diet and its relevance to social status, but also to explore the birds' habitats and environmental background, including commensalism and seasonal occurrence. This study highlighted differences between the four areas of Viljandi – the prehistoric rural settlement, historic castle, town, and suburb. We discuss diachronic trends in the utilisation of birds in these areas, largely determined by the 13th century Baltic Crusades and the transition from the Prehistoric to the Middle Ages, but also by population expansion and the social divergence that followed. In Prehistory, we witnessed more chicken exploitation, while wild birds seem to have played a smaller role. In the Historic Period, on the contrary, the utilised species are more diverse – probably to manifest social status. The main use of birds was for meat, eggs, and other products. Some species might have been used for hawking.